2017
DOI: 10.1177/1464884917730216
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform news consumption and its connections to civic engagement

Abstract: Studies of informational media use have focused on individual platforms or pitted platforms against each other when investigating their connections to civic engagement. This study offers evidence, collected in a 2016 survey of US adults, of how civically engaged individuals consume various types of news content across multiple platforms. Results suggest that the best condition is the most varied one, wherein consumers get news on all six platforms studied. A breakdown of content categories finds that televisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In addition, previous scholarly studies have also identified social capital as a potential mediating variable between news media and civic engagement (Collins, Neal, & Neal, 2014;Zhong, 2014). To summarize, a critical review of previous studies identified a significant relationship between news media use and civic engagement (Campbell & Kwak, 2010;Cheng, Liang, & Leung, 2015;Hao et al, 2014;Kim, 2007;Molyneux, 2017;Mushtaq & Baig, 2015). It is evident from previous scholarly studies that a significant relationship exists between news media and social capital, and social capital and civic engagement (Jalalani & Shah, 2019;Liu et al, 2014;Putnam, 2000;Warren, Sulaiman, & Jaafar, 2014).…”
Section: Direct and Indirect Effects Of Social Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous scholarly studies have also identified social capital as a potential mediating variable between news media and civic engagement (Collins, Neal, & Neal, 2014;Zhong, 2014). To summarize, a critical review of previous studies identified a significant relationship between news media use and civic engagement (Campbell & Kwak, 2010;Cheng, Liang, & Leung, 2015;Hao et al, 2014;Kim, 2007;Molyneux, 2017;Mushtaq & Baig, 2015). It is evident from previous scholarly studies that a significant relationship exists between news media and social capital, and social capital and civic engagement (Jalalani & Shah, 2019;Liu et al, 2014;Putnam, 2000;Warren, Sulaiman, & Jaafar, 2014).…”
Section: Direct and Indirect Effects Of Social Capitalmentioning
confidence: 99%
“…The results indicated a significant relationship between Facebook use and the civic activities of youth. Likewise, Molyneux (2017) argued that multiplatform news consumption plays a positive role in leading people towards civic engagement. Contrary to previous studies, Zubair and Halim (2017) found no relationship between the new media use and the civic contribution of youth.…”
Section: Literature Review News Media Use and Civic Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have found associations between personality type or personality traits and forms of civic engagement, and there is emerging interest in this area (Dinesen, Norgaard & Klemmensen, 2014). According to Molyneux (2017), "Television viewers and those who pay attention to breaking news and crime are less civically engaged". Banks (2017) describes the schools' role in reducing failed citizenship and helping marginalised groups become efficacious and participatory citizens in multicultural nation-states.…”
Section: Zabolotna and Pidhaietska (2021)mentioning
confidence: 99%
“…At the same time, time- and content-based patterns of information behaviour remain under-studied despite them being essential for the above-mentioned debates. Time-based reading habits influence the spread of information within the society and determine the amount of information received by the users from the news (Dunaway et al, 2018; Molyneux, 2019). Similarly, content-based reading habits define the composition of individual news repertoires and impact user engagement with the public sphere by informing (or not informing) them about societal matters (Kim, 2016; Molyneux, 2019; Taneja et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%